Normal Incidence of Sound Transmission Loss from Perforated Plates with Micro and Macro Size Holes - Putra, Azma; Ismail, Yusuf (Hindawi, 2014)
his paper studies the sound transmission loss of perforated panels and investigates the efect of the hole diameter on the sound insulation performance under normal incidence of acoustic loading. he hole diameters are distinguished into micro (submillimeter) and macro (millimeter) sizes. In general, the transmission loss reduces as the perforation ratio is increased. However, by retaining the perforation ratio, it is found that the transmission loss increases as the hole diameter is reduced for a perforate with micro holes due to the efect of resistive part in the hole impedance, which is contrary to the results for those with the macro holes. Both show similar trend at high frequency where the luid behavior inside the hole is inertial. Simple analytical formulae for engineering purpose are provided. Validation of the models with measurement data also gives good agreement.